Production of injection moulded 316L stainless steels reinforced with TiC(N) particles - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2008)
Metal matrix composites, based on 316L stainless steel and reinforced with TiC and TiCN particles, were manufactured following a powder injection moulding route: mixing, preparation of feedstock, moulding, debinding and sintering. The 316L stainless steel and carbide powders were dry mixed and moulded with wax based binder. The critical powder loading for injection moulding was 62.5 vol.-% for all samples. Binder debinding was performed by solvent and thermal method. After dedinding, the samples were sintered at 1250 and 1385 degrees C for 1 h in pure H-2. Metallographic studies were conducted to extend densification and the corresponding microstructural changes. The sintered samples were characterised by measuring tensile strength, hardness and wear behaviour. Wear loss was determined for all samples after wear tests. All powder, fracture surfaces of moulded and sintered samples, and worn surfaces of all the samples, were examined using scanning electron microscope. The sintered density of injection moulded 316L stainless steel samples, reinforced and unreinforced, increases with increasing sintering temperature. The addition of TiC and TiCN improves the hardness and wear resistance with increasing sintering temperature.
Keywords: Powder injection moulding; 316L stainless steel powder; TiC; TiCN; Mechanical properties; MATRIX COMPOSITES; ADDITIONS; CARBIDE; POWDER